Supporting Optimal Infant, Young Child and Maternal Nutrition and Health in Jordan: FY2021 3rd Quarter Report April 1st - June 30th, 2021. - Feed the Future Jordan Nutrition Innovation Lab. (Tufts University. Tisch Library., 2023)
The following is the quarterly report of the Feed the Future Jordan Nutrition Innovation Lab for the fiscal year 2021, starting from April 1st, 2021 until June 30th, 2021.; Keywords: nutrition, maternal and infant young child nutrition, human and institutional capacity, stakeholder engagement.; Leader with Associate Cooperative Agreement No. AID-OAA-LA-10-00006 Under Feed the Future Innovation Lab for Nutrition, Tufts University, Friedman School of Nutrition Science and Policy Cooperative Agreement Associate Award No.: 72027820LA00003.